PENGARUH BOARD INDEPENDENCE DAN MONITORING BY BOARD OF DIRECTORS TERHADAP WASTE DISCLOSURE - Ronika, Zakila Cahya; Erna Hernawati (Jurnal Akuntansi Trisakti, 2025)
This study aims to examine and analyze the influence of Board Independence and monitoring by the board of directors on waste disclosure. This quantitative research uses Fast Moving Consumer Goods (FMCG) companies listed on the Indonesia Stock Exchange from 2020 to 2023 as the population. A total of 256 samples from 80 companies were obtained through purposive sampling. The data were collected from sustainability reports and annual reports published on the Indonesia Stock Exchange and the companies’ official websites. The findings reveal that Board Independence has no effect on waste disclosure, while monitoring by the board of directors positively affects waste disclosure. These results contribute to a better understanding of corporate governance roles, particularly the board of directors, in enhancing sustainable environmental disclosure practices.